Absence of MeCP2 binding to non-methylated GT-rich sequences in vivo. Issue 7 (17th February 2020) - Connelly, John C; Cholewa-Waclaw, Justyna; Webb, Shaun; Steccanella, Verdiana; Waclaw, Bartlomiej; Bird, Adrian
Abstract: MeCP2 is a nuclear protein that binds to sites of cytosine methylation in the genome. While most evidence confirms this epigenetic mark as the primary determinant of DNA binding, MeCP2 is also reported to have an affinity for non-methylated DNA sequences. Here we investigated the molecular basis and in vivo significance of its reported affinity for non-methylated GT-rich sequences. We confirmed this interaction with isolated domains of MeCP2 in vitro and defined a minimal target DNA sequence. Binding depends on pyrimidine 5′ methyl groups provided by thymine and requires adjacent guanines and a correctly orientated A/T-rich flanking sequence. Unexpectedly, full-length MeCP2 protein failed to bind GT-rich sequences in vitro . To test for MeCP2 binding to these motifs in vivo, we analysed human neuronal cells using ChIP-seq and ATAC-seq technologies. While both methods robustly detected DNA methylation-dependent binding of MeCP2 to mCG and mCAC, neither showed evidence of MeCP2 binding to GT-rich motifs. The data suggest that GT binding is an in vitro phenomenon without in vivo relevance. Our findings argue that MeCP2 does not read unadorned DNA sequence and therefore support the notion that its primary role is to interpret epigenetic modifications of DNA.